Política da profanação: Walter Benjamin, linguagem e direito - SANTOS JUNIOR, Moacyr de Oliveira (2022)
This essay aims to unveil the theological aspects present in legal thought as a constitutive feature of its own functioning, demonstrating from language and political theology that Justice and Law are orders that do not keep any sense of belonging to each other. From Walter Benjamin's philosophy of history and language, I intend to articulate his messianic theology in such a way as to reveal the mythical rationality of Law in order to potentiate a discussion about justice and rights that can liberate them from the heritage of guilt. To this end, this monograph will investigate the interlocutions made by Benjamin regarding the centrality of language in the human relationship with the world, interpreting law as a plane of its irresolution and of the imprisonment of history by the mistranslation of social contents, culminating in the legal crystallization of surnamed versions of the historical struggles for rights. Thus, I intend to elaborate a conception of justice that moves from inside to outside of law; in a critical movement that can at the same time denounce the impossibility of its full realization within law, but also think of a political action capable of working at the limits of its fallibility, at the same time recognizing death and the finitude of living as presuppositions of a political happiness that is itself the historical and profane goal of the attentive critic, and enabling language and remembrance as categories that guarantee the possibility of this relationship.